Single mothers and poverty in Costa Rica - T. H. Gindling; Luis Oviedo (Institute for the Study of Labor (IZA), 2008)
Despite increasing average real family incomes in Costa Rica in the late 1990s and early 2000s, poverty rates did not fall. In this paper, we argue that during this period economic growth in Costa Rica did not translate into reduced poverty because of changes in family structure and in the labor market, and that these changes had an important gender dimension. Specifically, an increase in the proportion of Costa Rican households headed by single mothers led to an increase in the number of women with children entering the labor force. Many of these mothers, new entrants to the labor force, were unable or unwilling to find full-time work in the high-paying formal sector, and ended up unemployed or working part-time as self-employed workers. These labor market phenomena, in turn, contributed to low incomes for households vulnerable to poverty, especially those households headed by single mothers.
Keywords: I32; 300; Poverty; single mothers; employment; wages; Central America; Costa Rica; Armut; Alleinerziehende; Frauenerwerbstätigkeit; Teilzeitarbeit; Costa Rica